1997
DOI: 10.1093/emboj/16.10.2874
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal fingers of chicken GATA-2 and GATA-3 are independent sequence-specific DNA binding domains

Abstract: The GATA family of vertebrate DNA binding regulatory proteins are expressed in diverse tissues and at different times of development. However, the DNA binding regions of these proteins possess considerable homology and recognize a rather similar range of DNA sequence motifs. DNA binding is mediated through two domains, each containing a zinc finger. Previous results have led to the conclusion that although in some cases the N‐terminal finger can contribute to specificity and strength of binding, it does not bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 48 publications
1
62
0
Order By: Relevance
“…For instance, the N-terminal zinc fingers of GATA1, GATA2 and GATA3 recognize different DNA motifs and may contribute to their selectivity in binding target DNA sites. 26 Extensive studies using both in vitro and in vivo models demonstrate that the functions and downstream targets of GATA1 overlap with those of GATA2. 25,27,28 Moreover, in GATA1 knockout mice, GATA2 is upregulated to partially compensate for the loss of GATA1, and both GATA1 and GATA2 are critical for initiation of blood formation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the N-terminal zinc fingers of GATA1, GATA2 and GATA3 recognize different DNA motifs and may contribute to their selectivity in binding target DNA sites. 26 Extensive studies using both in vitro and in vivo models demonstrate that the functions and downstream targets of GATA1 overlap with those of GATA2. 25,27,28 Moreover, in GATA1 knockout mice, GATA2 is upregulated to partially compensate for the loss of GATA1, and both GATA1 and GATA2 are critical for initiation of blood formation.…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal finger mediates sequence-specific DNA binding (24 -26), whereas the N-terminal finger modulates DNA binding and contacts DNA with sequence specificity in certain contexts ( Fig. 2) (24,27,28). The zinc fingers interact with multiple coregulators, which are discussed below.…”
Section: Gata Factor-dependent Transcriptional Controlmentioning
confidence: 99%
“…These data differ from site selection experiments on the fulllength cGATA-2 where a distinct preference for AGATAA and AGATCT is reported (13), reflecting the binding properties of the C-terminal finger of GATA-2. Binding studies on the Nterminal finger of GATA-2 have shown that this peptide has a preference for the GATC motif, binding with a K d of 5 nM to AGATCT and a K d of 28 nM to AGATAA (10). Even though this difference in affinity is reflected partially in the selection experiments, in which AGATC is selected over AGATA in a 2.2:1 ratio (data not shown), an AGATCT site is not exclusively selected.…”
Section: Resultsmentioning
confidence: 97%
“…Published results have indicated that the N-terminal zinc finger of cGATA-2 binds to DNA with nanomolar affinities (10), suggesting that selection experiments with this peptide were feasible. However, unlike GATA-2, the N-terminal zinc finger of GATA-1 does not bind with high affinity to DNA (8,9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation